2015 IEEE Workshop on Automatic Speech Recognition and Understanding (ASRU) 2015
DOI: 10.1109/asru.2015.7404788
|View full text |Cite
|
Sign up to set email alerts
|

Improving data selection for low-resource STT and KWS

Abstract: This paper extends recent research on training data selection for speech transcription and keyword spotting system development. Selection techniques were explored in the context of the IARPA-Babel Active Learning (AL) task for 6 languages. Different selection criteria were considered with the goal of improving over a system built using a pre-defined 3-hour training data set. Four variants of the entropy-based criterion were explored: words, triphones, phones as well as the use of HMM-states previously introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…This method was used in [6] together with an N-best entropy based data selection. Finally, the study in [7] found that HMM-state entropy and letter density are good indicators of the utterance informativeness. Encouraging results were reported from the early attempts [2,3] with a 60% reduction of the transcription cost over Random Selection (RS).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This method was used in [6] together with an N-best entropy based data selection. Finally, the study in [7] found that HMM-state entropy and letter density are good indicators of the utterance informativeness. Encouraging results were reported from the early attempts [2,3] with a 60% reduction of the transcription cost over Random Selection (RS).…”
Section: Introductionmentioning
confidence: 95%
“…In this paper, we focus on conventional confidence-based AL as suggested in [2], although other studies [3,6,7] have shown some improvement over it. It is however worth highlighting that the details of the baseline confidence-based approach were not always clearly described, and that subsequent results were not in line with those reported in [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many of the previous works [21,22], the use of untranscribed data from the same language to improve the performance of the acoustic model in a low-resource language were studied. However, the use of transcribed data from closely related languages were not studied in detail.…”
Section: Borrowing Data or Pooling Datamentioning
confidence: 99%
“…In this case, the automatic transcripts are directly used for acoustic model training. 2) Data selection is also used to get relevant training data [4,5]. In contrast to SST, here the goal is to select data for which accurate manual transcripts will be created.…”
Section: Introductionmentioning
confidence: 99%